THE PEN IS MIGHTIER THAN THE SCALPEL: THE CASE FOR ELECTRONIC MEDICAL RECORDS# - Hartmann, D.; Sooklal, S. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: A case study evaluated how physical medical records are managed and curated at a large tertiary hospital. It was found that the current microfiching technology was outdated, ineffective, and in many cases an impediment to appropriate care. Alternative record-keeping techniques were evaluated. A proposal for a localised electronic medical record (EMR) system, disseminated by tablet computer, is presented in this paper. Issues about ethics and access to information are explored, and some of the issues that have affected global implementation are highlighted. AFRIKAANSE OPSOMMING: